2012
DOI: 10.1177/1479164112459663
|View full text |Cite
|
Sign up to set email alerts
|

Hyperglycaemia in acute lacunar stroke: A Chinese hospital-based study

Abstract: Admission hyperglycaemia is very common in acute ischaemic stroke (IS) patients and is associated with worse outcome in non-lacunar infarction, but its association with lacunar infarction remains controversial. We investigated the association between hyperglycaemia and clinical outcome in patients with acute lacunar stroke in a hospitalised Chinese population. Consecutive patients with acute IS were enrolled and classified into lacunar and non-lacunar stroke groups based on clinical criteria according to the O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 42 publications
2
10
0
Order By: Relevance
“…This result differs from the findings presented by Fang et al[ 24 ], although it is partially consistent with findings from several other previous studies[ 9 , 10 , 25 , 26 ]. Fang et al suggested that hyperglycemia was not associated with functional outcome in patients with lacunar stroke[ 24 ]. One explanation for this difference is that they measured fasting glucose levels, which may be affected by confounding variables[ 11 ].…”
Section: Discussionsupporting
confidence: 82%
“…This result differs from the findings presented by Fang et al[ 24 ], although it is partially consistent with findings from several other previous studies[ 9 , 10 , 25 , 26 ]. Fang et al suggested that hyperglycemia was not associated with functional outcome in patients with lacunar stroke[ 24 ]. One explanation for this difference is that they measured fasting glucose levels, which may be affected by confounding variables[ 11 ].…”
Section: Discussionsupporting
confidence: 82%
“…Patients with hyperglycemia did not have larger perfusion deficits in ischaemic stroke 19 . Hyperglycemia was found not to associate with functional outcome in lacunar stroke 20 . Therefore, our finding suggested hyperglycemia can reduce the infarct volume of lacunar stroke in both the cortex and sub-cortical regions.…”
Section: Discussionmentioning
confidence: 71%
“…Admission hyperglycaemia was very common in AIS patients and was related to worse prognosis in non-lacunar brain infarction. The association between hyperglycaemia and clinical outcome in 689 consecutive lacunar AIS patients in a hospitalized Chinese population was investigated (11). Of them, 159 (23%) presented with diabetes mellitus.…”
Section: Discussionmentioning
confidence: 99%